Пухлини надниркових залоз: діагностика та сучасні хірургічні, зокрема малоінвазійні, методи лікування - Павловський, М. П.; Бойко, Н. І.; Гавриш, Я. І. (Clinical Endocrinology and Endocrine Surgery, 2011)
The article analyzed the results of diagnosis and treatment of 759 patients (aged from 8 to 78 years) with adrenal tumors. A variety of clinical symptoms depended on the adrenal layer lesion. We analyzed the results of biochemical and instrumental methods of examination of patients, hormone blood levels, methods of preoperative preparation of patients, postoperative complications, and results of minimally invasive surgery. From 1997 till 2010 we performed 81 endoscopic adrenalectomies.